2017
DOI: 10.1177/1359457517728379
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the present, re-visioning the future: An initial mapping of music therapists in the United Kingdom

Abstract: Background: Music therapy is a small, but evolving profession. Numbers of music therapists are increasing, yet little is known regarding the workforce and its employment characteristics. To understand the current profile of the music therapy workforce in the United Kingdom (UK), the British Association for Music Therapy (BAMT) commissioned a national survey of its membership. Aim: This survey explores the profile of the UK music therapy workforce in terms of demographics, training and employment characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Catherine Carr’s review of practice in the United Kingdom found despite UK trainings having a shared focus on improvisational music therapy, the training programmes vary in their theories and approaches. ‘This plurality, which is equally reflected in practitioners’ diverse identities and ways of practicing, is further enhanced by other emerging trainings’ (Carr et al, 2017: 69).…”
Section: Definingmentioning
confidence: 99%
“…Catherine Carr’s review of practice in the United Kingdom found despite UK trainings having a shared focus on improvisational music therapy, the training programmes vary in their theories and approaches. ‘This plurality, which is equally reflected in practitioners’ diverse identities and ways of practicing, is further enhanced by other emerging trainings’ (Carr et al, 2017: 69).…”
Section: Definingmentioning
confidence: 99%
“…It is estimated that more than half of all registered arts therapists in the United Kingdom are working with children and young people (Karkou, 2010), which may vary for the different types of arts therapies. In music therapy, the latest workforce survey (Carr et al, 2017) showed that schools were the most commonly reported setting, while working with children and adolescents was the most commonly reported post (78% of all posts). In art therapy, a current workforce survey (British Association of Art Therapists (BAAT), 2018) showed that 68% of all art therapies were working with children and young people, while 35% of them were based in school-based settings.…”
Section: Introductionmentioning
confidence: 99%
“…There are many possible theoretical lenses that could be used to interpret and understand the HCPC (2013) SoPs. With the prevalence of music therapy practice undertaken with individuals who experience disablement in the United Kingdom (Carr et al, 2017), critical disability studies is proposed as a valid perspective to consider in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The professional regulation of the discipline of music therapy in 1997 by the then Council for Professions Supplementary to Medicine (CPSM) and subsequently the HCPC in 2012 are recognised by many as important milestones in the evolution of the profession (Barrington, 2005(Barrington, , 2008(Barrington, , 2015Bunt and Hoskyns, 2002;Carr et al, 2017;Karkou et al, 2017;Odell-Miller, 2016). With this professionalisation comes a range of criteria, considerations and context aligned with the regulatory body and allied professions.…”
Section: Introductionmentioning
confidence: 99%